Access to physiotherapy services in South African settings: stretching a hand to under-resourced communities with students as agents of change - Sekome, Kganetso; Sujee, Laeeqa; Tomes, Lauren; Pilusa, Sonti (Frontiers in Rehabilitation Sciences, 2023)
Background: Physiotherapy is a healthcare profession that is known to enhance human functioning and prevent further disability. Other physiotherapy roles include promoting health, wellbeing and prevention of diseases. In the South African context, physiotherapy and rehabilitation services are largely accessed by those living in urban communities and those with private medical funding. Although rehabilitation is an essential component of the package of care, rehabilitation services do not reach disadvantaged communities who also need them. Physiotherapy students training can play a vital role in improving rehabilitation access to vulnerable communities through equitable provision of service-learning. Aim: This paper illustrates how physiotherapy students training at a South African university practice to provide equitable services disadvantaged rural and urban communities. Discussion: The first and second training years focuses on theoretical and classroom-based learning where students gain an understanding of basic principles of inclusion, equity, diversity, and self-awareness. In later years students provide community-based services at urban and rural communities with a focus on increasing access to rehabilitation services in an equitable manner. Principles of public health and community rehabilitation guide the clinical objectives of which the students fulfil. Poor access to rehabilitation services was highlighted during the COVID-19 pandemic, we provide a case study to demonstrate the roles physiotherapy students played to fill this gap. The authors offer a reflection from their involvement in physiotherapy student training and provide an example of a moment which displayed equity, diversity, and inclusion in their career. Conclusion: There is a huge gap to fill in the provision of equitable rehabilitation services for the South African population. Institutions responsible for the training of physiotherapy or any rehabilitation profession should realize their role in service delivery through a service-learning approach.